How mobile NMR can help with the conservation of paintings. (23rd July 2020) - Awad, Wegood M.; Baias, Maria
Abstract: The conservation of paintings is fundamental to ensure that future generations will have access to the ideas of the grand masters who created these art pieces. Many factors, such as humidity, temperature, light, and pollutants, pose a risk to the conservation of paintings. To help with painting conservation, it is essential to be able to noninvasively study how these factors affect paintings and to develop methods to investigate their effects on painting degradation. Hence, the use of mobile nuclear magnetic resonance (NMR) as a method of investigation of paintings is gaining increased attention in the world of Heritage Science. In this mini‐review, we discuss how this method was used to better understand the stratigraphy of paintings and the effect different factors have on the painting integrity, to analyze the different cleaning techniques suitable for painting conservation, and to show how mobile NMR can be used to identify forgeries. It is also important to keep in mind its limitations and build upon this information to optimize it to extend its applicability to the study of paintings and other precious objects of cultural heritage. Abstract : This mini‐review focuses on the use of mobile NMR in the analysis of paintings. Relevant examples from the scientific literature have been used to exemplify the applications of mobile NMR in various aspects of painting research. Some of the examples reveal details about the analysis of stratigraphy and pigments, investigating different cleaning methods and understanding the aging of paintings.